2010
DOI: 10.1038/ijo.2010.111
|View full text |Cite
|
Sign up to set email alerts
|

Fat-free mass index: changes and race/ethnic differences in adulthood

Abstract: Objective Nutritional status is assessed by measuring BMI or percent body fat (%fat). BMI can misclassify persons who carry more weight as fat-free mass and %fat can be misleading in cases of malnutrition or in disease states characterized by wasting of lean tissue. The fat-free mass index (FFMI) is proposed to assess body composition in individuals who have a similar body composition but differ in height allowing identification of those suffering from malnutrition, wasting or those that possess a relatively h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 19 publications
2
56
1
1
Order By: Relevance
“…37,38 In addition, the relationship between fat and lean mass is known to be influenced by ethnicity. 18 As we only investigated Caucasians, our results are not transferable to other ethnic groups.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…37,38 In addition, the relationship between fat and lean mass is known to be influenced by ethnicity. 18 As we only investigated Caucasians, our results are not transferable to other ethnic groups.…”
Section: Discussionmentioning
confidence: 76%
“…17 In women, FFMI was consistently lower with increasing age group after the age of 20 years, whereas in men this occurred after the age of 40 years (Figures 1a and b). By contrast, Hull et al 18 showed FFMI to peak with age 45 years in women and 25 years in men with a subsequent decrease thereafter. Barlett et al 19 demonstrated the ratio of FFM/height to remain stable till age 50 years in women with a decrease afterwards and a nonsignificant decline in men 460 years.…”
Section: Discussionmentioning
confidence: 88%
“…The study by Hull et al 9 also reported a curvilinear relationship between age and FFMI for both genders, and that there was a gender difference in the rate of change in FFMI with age. Declines in FFMI were found at an earlier age in male subjects, whereas decline in female subjects occurred in the late 40s.…”
Section: Ffmi Across Adult Agementioning
confidence: 90%
“…8 As pointed out by Hull et al, 9 in hospitalized individuals, recognition of malnutrition inferred from BMI is particularly important because nutritional status is related to longevity and mortality, influences the course of a disease and optimal treatment and affects the length of hospital stay. By comparing values of an individual patient with national norms, the health professional is able to assign a level of fatness, determine the level of risk for chronic disease and estimate mortality risk.…”
Section: Superficial Deepmentioning
confidence: 99%
See 1 more Smart Citation